Epithelial–mesenchymal transition: an organizing principle of mammalian regeneration - Bedelbaeva, Kamila; Cameron, Benjamin; Latella, John; Aslanukov, Azamat; Gourevitch, Dmitri; Davuluri, Ramana; Heber-Katz, Ellen (Frontiers in Cell and Developmental Biology, 2023)
The MRL mouse strain is one of the few examples of a mammal capable of healing appendage wounds by regeneration, a process that begins with the formation of a blastema, a structure containing de-differentiating mesenchymal cells. HIF-1α expression in the nascent MRL wound site blastema is one of the earliest identified events and is sufficient to initiate the complete regenerative program. However, HIF-1α regulates many cellular processes modulating the expression of hundreds of genes. A later signal event is the absence of a functional G1 checkpoint leading to G2 cell cycle arrest with increased cellular DNA but little cell division seen in the blastema. This lack of mitosis in MRL blastema cells is also a hallmark of regeneration in classical invertebrate and vertebrate regenerators such as the planaria, hydra, and newt. Here, we explore the cellular events occurring between HIF-1α upregulation and its regulation of the genes involved in G2 arrest (EVI-5, γH3, Wnt5a, and ROR2), and identify EMT (Twist, Slug) and chromatin remodeling (EZH-2 and H3K27me3) as key intermediary processes. The locus of these cellular events is highly regionalized within the blastema, occurring in the same cells as determined by double staining using immunohistochemistry and FACS analysis, and appear as EMT and chromatin remodeling followed by G2 arrest determined by kinetic expression studies.